SISTEM PENGAMBILAN KEPUTUSAN UNTUK MENENTUKAN LAMA MASA STUDI DAN IPK MENGGUNAKAN METODE FUZZY TAHANI (Jurnal Pelangi : Research of Education and Development, 2014)
In accordance with the demands of the academic accreditation or accreditation forms STKIP PGRI West Sumatra requires data on how long the period of study the student and indexstudent achievement when completing educationpresentation of these data can be difficult in a system to analyze the data because it does not exist, the authors conducted research on decision-making system to determine how long the period of study and indexstudent achievement with fuzzy Tahani database where all the data contained in the database of academic portal campus.